The Montessori Method and Minnesota Academic Standards in Mathematics Prioritized by Saint Paul Public Schools - Richards, McKenna (My University, 2015)
Montessori education is a widely misunderstood teaching philosophy. Many in the world acknowledge and value the success of Montessori programs, yet are unaware of the learning support that can result from the use of beautiful manipulative materials used in a carefully structured Montessori classroom environment. Public schools are beginning to adopt this method before becoming equipped and educated on the philosophy. This study was performed in a public Montessori school in the Midwest with twelve kindergarten students learning mathematic skills through Montessori materials provided to the classroom. The Montessori materials in this classroom were aligned with the standards that the district found pertinent to the success of the students. The assessments given to the students were the same assessments that all of the kindergarten students in this district were given. For example one of the learning targets is, ?I can count to 20 with objects,? 100% of the students met the district expectation for this skill. If Montessori schools begin to align materials to the standards that are valued in society and prove that the method is successful through the same tests given to students who learn in a traditional model, the effectiveness of this pedagogical approach to maximize students? learning will be more widely recognized.